The effects of copper-loaded montmorillonite on intestinal morphology, microbiota, barrier function, antioxidant capacity, and gut-related gene expression in broilers - Xinru Hu; Yiwen Rao; Peiqianng Yuan; Xingyong Chen; Cheng Zhang (Poultry Science)
Intestinal health is pivotal in modern poultry production, profoundly influencing growth performance and disease resistance. This study evaluated copper-loaded montmorillonite (Cu-MMT) as a novel feed additive to enhance gut health in broilers. A 21-day experiment was conducted using 270 one-day-old Arbor Acres broilers, randomly divided to three dietary treatments: a basal diet, a group supplemented with 350 mg/kg MMT, and a group supplemented with 350 mg/kg Cu-MMT. The results revealed that dietary supplementation with Cu-MMT significantly decreased the abundance of intestinal pathogens (Salmonella, Escherichia coli, and Clostridia). Concurrently, improvements in intestinal morphology were observed with Cu-MMT supplementation, characterized by elevated villus height and a higher villus height-to-crypt depth ratio. Furthermore, it reduced serum biomarkers of intestinal permeability (diamine oxidase and D-lactic acid), while upregulating the mRNA abundance of tight junction proteins (Zonula occludens-1 and occludin) and mucin-2. Furthermore, Cu-MMT outperformed MMT alone in promoting nutrient utilization, elevating digestive enzymes (amylase, lipase, trypsin) activities, and upregulating key nutrient transporters (PepT1, Bo,+AT, ATBo,+, y+LAT2, and LAT1). The Cu-MMT supplementation significantly bolstered antioxidant defenses and mucosal immunity, as reflected by increased activities of superoxide dismutase and glutathione peroxidase (GSH-Px), reduced malondialdehyde concentrations, and increased mRNA abundance of GSH-Px and mucosal secretory immunoglobulin A. Mechanistically, the beneficial effects of Cu-MMT on antioxidant capacity were primarily mediated through the activation of the nuclear factor erythroid 2-related factor 2 signaling pathway. In conclusion, Cu-MMT enhances the growth of broilers by enhancing intestinal barrier integrity, modulating gut microbiota, augmenting intestinal antioxidant capacity and promoting intestinal digestion and absorption functions, making it a promising feed additive.